2502. Host Susceptibility to Andes Hantavirus Infection Associates to a Single Nucleotide Polymorphism at the αVβ3 Integrin. (26th November 2018) - Martinez-Valdebenito, Constanza; Ferres, Marcela; Corre, Nicole Le; Angulo, Jenniffer; Vial, Cecilia; Vial, Pablo; Mertz, Gregory; Valdivieso, Francisca; Galeno, Hector; Villagra, Eliecer; Vera, Lilian; Lagos, Natalia; et al.
Abstract: Background: ANDV is etiologic agent of hantavirus cardiopulmonary syndrome (HCPS) in Chile. Transmission occurs mainly by exposure to aerosolized excretes of infected rodents, person-to-person transmission has also been reported. ANDV infected endothelial cell through αV, β3 integrin at plexin-semaphorin-integrin (PSI) domain. In vitro assays establish that the change from leucine to proline, at residues 33 in PSI-domain inhibits ANDV recognition of integrin. Here we assessed the risk that represents a polymorphism leucine to proline (L33P) and the association to susceptibility to ANDV. Methods: For risk assessment, 74 cases and 105 controls (exposed but not infected) were genotyped by Taqman assay, epidemiological and demographic data were recorded. We also evaluated SNP distribution at general population, infected population (serum collection) and 11 prospectively diagnosed ANDV cases. A regression logistic model was used to assess environmental or person to person risks factors of hantavirus infection either in presence or absence of the "susceptible" or "protective" genotypes. Results: In cases and controls the susceptible (TT) genotype (Leucine) was distributed in an 89.2 and 60%, respectively (Figure 1). The protective genotype (CC) was absent among cases but present at 11.4% in exposed controls. We estimated the Odds ratio (OR), through a logistic model, first using only previously described risk activities and after adding the genotype TT; the OR increased from 6.2 to 12.6. Cases and control at same exposure (access to abandoned place) showed that controls have a 57% of TT genotype, meanwhile in cases was 91%, with an OR of 7.3. For a second common exposure activities (handle woods) the controls had a 59.4% of TT genotype, meanwhile for cases 85%. For general and infected population both did not show statistical differences in allele distribution, and we detected a 1.7% of CC genotype in the infected population (Figure 2). We did not detected CC genotypes in the eleven prospective ANDV cases. Conclusion: There was association between this particular SNP and infection susceptibility to ANDV. We highlight the relevance of genetic background in host-virus interaction. Nevertheless, other factors such as innate immune system or viral variability must be explored to fully understand the disease pathogenesis. Disclosures: C. Martinez-Valdebenito, FONDECYT1161197: Grant Investigator, Educational grant. ACT1408: Grant Investigator, Research grant. M. Ferres, FONDECYT1161197: Grant Investigator, Research grant. ACT1408: Grant Investigator, Research grant. N. Le Corre, FONDECYT1161197: Grant Investigator, Research grant. ACT1408: Grant Investigator, Research grant. J. Angulo, FONDECYT1161197: Grant Investigator, Research grant. ACT1408: Grant Investigator, Research grant.